Structural formulation and self-oscillation prediction in multidimensional nonlinear closed-loop autonomous systems - Patra, Kartik C.; Pati, Bibhuti B.; Łozowicki, Adam (Zielona Góra: Uniwersytet Zielonogórski)
This paper describes the structure of a general two-dimensional nonlinear closed-loop system and application of the universal chart, leading to the use of computer graphics, for a systematic analysis of the complex problem of predicting selfoscillations (limit cycles). The graphical approach provides an explicit and novel insight into the conditions for the occurrence of limit cycles in such systems.
Keywords: universal chart; phasor diagram; limit cycles; multidimensional; nonlinear systems; describing function